What is Libra? - Cawrey, Daniel (O'Reilly Media, 2020)
Facebook recently announced Libra, an ambitious project to bring blockchain-based cryptocurrency technology to its users around the world. This large-scale project involves a consortium of organizations in technology and finance hoping to reimagine digital finance. With this report, you'll explore the promises and challenges Facebook and its stakeholders face as Libra approaches its expected 2020 launch. Once it arrives, Libra could have a huge impact on finance and consumer banking. What does it mean for average people using financial services? How could Libra impact the global finance and technology sectors? Author Daniel Cawrey (Mastering Blockchain) takes you through the issues and possibilities. Learn how: Libra will leverage blockchain, cryptocurrency, and smart contracts within Facebook's existing platforms A consortium of organizations across business, technology, and nonprofits will govern Libra Facebook's Calibra digital wallet will work within this ecosystem Libra took ideas from Bitcoin and the greater blockchain community The system needs to scale to billions of users if it is to work across many devices and networks Libra could help people with little or no access to the banking system.